Time-of-day effects in implicit associations are probably selection effects, not circadian rhythms - Schofield, Timothy P (PeerJ PrePrints, 2015)
Time-of-day effects in human psychological functioning have been known of since the 1800s. However, outside of those specifically focused on the quantification of circadian rhythms, they have largely been neglected. Moves toward online data collection now mean that psychological investigations take place around the clock, which affords researchers the ability to easily study time-of-day effects. Recent analyses have shown, for instance, that implicit attitudes have time-of-day effects. The plausibility that these effects indicate circadian rhythms rather than selection effects is considered in the current study. There was little evidence that the time-of-day effects in implicit attitudes shifted appropriately with factors known to influence circadian rhythms, and even variables that cannot logically show circadian rhythms demonstrated stronger time-of-day effects than did implicit attitudes. Taken together, these results suggest that time-of-day effects in implicit attitudes are more likely to represent selection effects rather than circadian rhythms, but do not rule out the latter possibility.
Keywords: internet research; implicit attitudes; circadian rhythms; methods; cosinor regression; selection effects; IAT